Brain functional activity of Parkinson’s disease patients under a virtual reality eye movement task: a functional near-infrared spectroscopy study - Liu, Yanzhi; Shi, Ziqian; Wang, Lifeng; Yang, Chuyan; Wang, Xinyan; Lin, Yongzhong; Qi, Liping (Frontiers in Human Neuroscience, 2025)
ObjectiveThis study aimed to investigate the eye movement behavior characteristics and associated brain functional activity changes in Parkinson’s disease (PD) patients during a complex visual task, using virtual reality (VR) eye movement tasks combined with functional near-infrared spectroscopy (fNIRS) technology.MethodsA total of 27 PD patients and 29 healthy controls were included in the study. Participants performed a “Whack-a-Mole” eye movement task on a VR platform. Fixation time and task error rates were recorded, and fNIRS was used to measure changes in brain oxygenation. The differences in oxygenated hemoglobin concentration in brain regions between PD patients and healthy controls were assessed during task performance.ResultsThe PD group exhibited a significantly higher task error rate compared to the control group (p = 0.02), and a significantly longer mean fixation time (p = 0.001). fNIRS results revealed that the PD group had considerably higher oxygenated hemoglobin concentrations in the bilateral primary visual cortex (V1), visual association cortex, primary somatosensory cortex (S1), and auditory cortex compared to the control group (p < 0.05).ConclusionPD patients exhibit significant eye movement behavioral impairments during the execution of complex visual tasks, accompanied by compensatory brain functional activation in relevant brain regions. These findings provide important insights for the early diagnosis and therapeutic intervention of PD.